Decentralized feedback controllers for uncertain interconnected systems with Markovian jumping parameters - Boukas, El-Kebir; Świerniak, Andrzej (1950- ); Yang, Hailang (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the problem of design of decentralized controllers for a class of interconnected linear systems with Markovian jumping parameters and unknown but structured uncertainties. Results of Trinh and Aldeen (1993) are extended to a stochastic class of piecewise deterministic systems.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka